Unit-Level Counterproductive Work Behavior (CWB): A Conceptual Review and Quantitative Summary - Carpenter, Nichelle C.; Whitman, Daniel S.; Amrhein, Rachel (Journal of Management, 2021)
Despite assumptions that counterproductive work behavior (CWB) leads to detrimental outcomes for organizations, most of the existing CWB research focuses on outcomes for the individual employee. In the present study, we clarify fundamental issues regarding unit-level CWB, including its definition and how it is distinct from individual-level CWB. We then use social information-processing (SIP) theory as a lens to articulate our hypotheses regarding the factors associated with unit-level CWB’s emergence (e.g., collective attitudes, human resources practices, leadership) as well as its relationship with unit-level performance (e.g., profit, customer satisfaction). We use meta-analysis (representing 7,110 units and over 391,000 employees) to test our hypotheses. Our results show that unit-level CWB is significantly related to antecedents such as collective job attitudes, the use of strategic human resource management practices (e.g., staffing, training, rewards), and collective perceptions of the work environment (e.g., unit-level fairness perceptions). Moreover, we demonstrate that unit-level CWB is empirically linked to unit-level productivity (ρ = −.23), turnover (ρ = .22), customer satisfaction (ρ = −.26), and profit (ρ = −.31), which verifies the detrimental consequences of CWB at the strategic level. We conclude with a detailed discussion of the theoretical and practical implications of this study as well as a clear plan for future research.